Peran Kebijakan Fiskal dalam Mendorong Pembangunan Infrastruktur di Indonesia: Studi Kasus Tahun 2023 - Salsabila, Mella Adzkia; Musyafi`i, Ahmad Riyan (Journal of Economics and Social Sciences (JESS), 2024)
Introduction/Main Objectives: Infrastructure development is crucial for driving economic growth and societal well-being in Indonesia. Fiscal policy, particularly government spending and taxation, plays a central role in supporting infrastructure projects. However, the impact of fiscal policy on infrastructure development in Indonesia, especially in 2023, remains underexplored. This study aims to analyze the influence of fiscal policy on infrastructure development. Research Methods: Using a qualitative approach with a literature review, this research examines relevant journals, government reports, and official documents on fiscal policy and infrastructure development. The analysis focuses on fiscal expenditure and tax policies that impact infrastructure investment. Finding/Results: The findings reveal that increased fiscal spending on infrastructure and tax reforms have significantly contributed to accelerating infrastructure development in Indonesia. The effectiveness of these policies has enhanced investment and the quality of infrastructure projects. Additionally, collaboration between central and local governments has been identified as a crucial factor for successful implementation. Conclusion: In conclusion, effective fiscal policies, improved coordination, and refined tax policies are crucial for efficient infrastructure development and economic growth in Indonesia.